Association of Arterial Oxygen Tension During In-Hospital Cardiac Arrest With Return of Spontaneous Circulation and Survival. (July 2018) - Patel, Jignesh K.; Schoenfeld, Elinor; Parikh, Puja B.; Parnia, Sam
Background: Despite numerous advances in the delivery of resuscitative care, in-hospital cardiac arrest (IHCA) continues to be associated with high morbidity and mortality. We sought to study the impact of arterial oxygen tension (Pao2 ) on return of spontaneous circulation (ROSC) and survival to discharge in patients with IHCA. Methods: The study population included 255 consecutive patients who underwent advanced cardiac life support–guided resuscitation from January 2012 to December 2013 for IHCA at an academic tertiary medical center. Of these patients, 167 underwent arterial blood gas testing at the time of the arrest. Baseline demographic, clinical, laboratory, and clinical outcome data were recorded. The primary outcome of interest was survival to hospital discharge. Secondary outcome of interest was presence of ROSC. Results: Of the 167 patients studied, Pao2 categorization included the following: Pao2 < 60 mm Hg (n = 38), Pao2 of 60-92 mm Hg (n = 44), Pao2 of 93 to 159 mm Hg (n = 43), Pao2 of 160 to 299 mm Hg (n = 24), and Pao2 ≥ 300 mm Hg (n = 18). Patients with higher Pao2 levels during the time of cardiac arrest were noted to have higher rates of hypertension and chronic kidney disease. Clinical presentation of IHCA, in particular, the initial rhythm, location of IHCA, and duration of cardiopulmonary resuscitation, was similar in all groups. Patients with higher Pao2 levels had higher platelet count, higher arterial pH, and lower arterial carbon dioxide tension (Pco 2 ). With respect to outcomes, patients with higher intra-arrest Pao2 levels had progressively higher rates of ROSC (58% vs 71% vs 72% vs 79% vs 100%, P = .021) and survival to discharge (16% vs 23% vs 30% vs 33% vs 56%, P = .031). In multivariate analysis, Pao2 ≥ 300 mm Hg was independently associated with higher survival to discharge (odds ratio 60.68; 95% confidence interval: 3.04-1210.28; P = .007; referent Pao2 < 60 mm Hg). Conclusion: Higher intra-arrest Pao2 is independently associated with higher rates of survival to discharge in adults with IHCA.